2016
DOI: 10.1177/0003702815626673
|View full text |Cite
|
Sign up to set email alerts
|

Bacterial Suspensions Deposited on Microbiological Filter Material for Rapid Laser-Induced Breakdown Spectroscopy Identification

Abstract: Four species of bacteria, E. coli, S. epidermidis, M. smegmatis, and P. aeruginosa, were harvested from agar nutrient medium growth plates and suspended in water to create liquid specimens for the testing of a new mounting protocol. Aliquots of 30 µL were deposited on standard nitrocellulose filter paper with a mean 0.45 µm pore size to create highly flat and uniform bacterial pads. The introduction of a laser-based lens-to-sample distance measuring device and a pair of matched off-axis parabolic reflectors fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 20 publications
0
20
0
Order By: Relevance
“…The linear dependence of the total LIBS emission intensity with concentration was confirmed in 2018 by Liao et al who demonstrated this for both E. coli and S. aureus concentrations spanning four decades, from 10 4 CFU/mL up to 10 8 CFU/ml with R 2 values greater than 0.97 [51]. Malenfant et al also reported a linear dependence of the total LIBS emission intensity on the cell concentration when a large number of cells were deposited on a nitrocellulose filter testing medium [70]. In this study, approximately 10 5 cells were ablated per laser shot.…”
Section: Concentration/titermentioning
confidence: 82%
See 3 more Smart Citations
“…The linear dependence of the total LIBS emission intensity with concentration was confirmed in 2018 by Liao et al who demonstrated this for both E. coli and S. aureus concentrations spanning four decades, from 10 4 CFU/mL up to 10 8 CFU/ml with R 2 values greater than 0.97 [51]. Malenfant et al also reported a linear dependence of the total LIBS emission intensity on the cell concentration when a large number of cells were deposited on a nitrocellulose filter testing medium [70]. In this study, approximately 10 5 cells were ablated per laser shot.…”
Section: Concentration/titermentioning
confidence: 82%
“…1513 spectra were classified using both DFA and PLS-DA in an externally validated classification. Both algorithms possessed sensitivities and specificities greater than 97% in a four-genus library composed of Escherichia, Staphylococcus, Pseudomonas, and Mycobacterium [70].…”
Section: Discriminant Function Analysis / Partial Least Squaresmentioning
confidence: 99%
See 2 more Smart Citations
“…As yet, there is no FDA-cleared LIBS system for rapid identification of pathogen microorganisms. 51,52 Raman spectroscopy…”
Section: Laser-induced Breakdown Spectroscopymentioning
confidence: 99%